A rare association of squamous cell carcinoma with paraneoplastic pemphigus - Ramapure, Raavi; Gulhane, Vaishnavi; Jawade, Sugat; Singh, Adarshlata; Madke, Bhushan (Journal of Pakistan Association of Dermatologists, 2022)
Pemphigus vulgaris is an auto-immune blistering disorder associated with splitting at the dermo-epidermal junction. It targets the desmoglein structural protein of skin thus causing formation of blisters. It is seen to be associated with esophageal and laryngeal malignancies. Here in this case report, we try to highlight the unusual presentation of squamous cell carcinoma of buccal mucosa with pemphigus vulgaris.